2016
DOI: 10.1007/s11239-016-1385-9
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with extended-interval warfarin monitoring

Abstract: Extended-interval monitoring of warfarin has been proposed to reduce follow-up burden and improve patient satisfaction. We aimed to make an initial assessment of anticoagulation satisfaction before and after an extended-interval warfarin monitoring intervention. We conducted a translational prospective single-arm pilot study of extended-interval warfarin monitoring in five pharmacist-managed anticoagulation clinics. Patients meeting CHEST guideline criteria for extended-interval warfarin monitoring began progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 32 publications
1
14
0
2
Order By: Relevance
“…According to these authors, patients who switch from conventional care to the self-care model after 2 years have a significantly higher QoL, probably because they are less dependent on going to the doctor. In contrast, Carris et al found that anticoagulation satisfaction following extended interval monitoring, as measured by the DASS questionnaire, did not change or may have marginally worsened after an extended interval follow up, which was contrary to expectations [16]. The authors suggest that less frequent feedback and patient-provider interaction might have resulted in reduced patient perception of benefit from anticoagulation and reduced self-management activities [16].…”
Section: Discussionmentioning
confidence: 94%
“…According to these authors, patients who switch from conventional care to the self-care model after 2 years have a significantly higher QoL, probably because they are less dependent on going to the doctor. In contrast, Carris et al found that anticoagulation satisfaction following extended interval monitoring, as measured by the DASS questionnaire, did not change or may have marginally worsened after an extended interval follow up, which was contrary to expectations [16]. The authors suggest that less frequent feedback and patient-provider interaction might have resulted in reduced patient perception of benefit from anticoagulation and reduced self-management activities [16].…”
Section: Discussionmentioning
confidence: 94%
“…One other health system has published their experience with a similar de-implementation effort to reduce frequent INR tests among patients with stable warfarin control [16, 17]. However, they did not report on how frequently their staff scheduled the next INR test more than the standard 4 weeks into the future for eligible patients or the barriers and facilitators to their de-implementation effort.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire has been extensively used with patients with AF or other diseases requiring anticoagulant treatment. [31][32][33][34][35] It has been translated into Brazilian Portuguese, and the cultural validation demonstrated very good psychometric properties (Cronbach's α = 0.79). 36 In some studies, the Duke questionnaire was used as a quality-of-life measure, and the authors demonstrated that dissatisfaction with anticoagulant treatment contributed to lower adherence, worse INR control and worse clinical outcomes.…”
Section: Adherence Measures Applicable To Afmentioning
confidence: 99%